Current Status of Reproductive Performance and Problems in Dairy Animals of Gujarat and their Amelioration including Study of Fertility Gene Markers - Dhami, Arjan J.; Parmar, Sanjay C.; Patel, Jagadish A.; Hadiya, Kamlesh K.; Joshi, Rajesh S.; Sarvaiya, Nitesh P. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The surveillance of breedable 4711 zebu cattle, 8416 crossbred cattle and 15688 buffaloes (total 28,815) from 5 different regions of  Gujarat revealed reproductive problems in 27.4, 26.6 and 34.5 % animals, respectively. Reproductive performance, reproductive problems,  feeding, and housing practices varied among different classes of animals in different regions. Natural service was still the major means  of breeding cattle and buffaloes in Saurashtra and Kutch region, while in middle, north and south Gujarat AI has been practiced for  70-90% breeding. Blood glucose, biochemical and minerals profile of infertile animals also varied greatly in different regions, and it  was significantly improved following supplementations of chelated ASMM and bypass fat for 30-45 days. Among so called infertile  animals (7390), the incidence of anestrus was maximum (23.34%) followed by repeat breeding (14.94%), subestrus (14.69%), uterine  infection (12.91%), infantile genitalia/pubertal anestrus (9.64%), pregnancy or estrus (10.63%) and others (13.83%). Supplementation  of minerals in combination with bypass fat in anestrus animals resulted in enhanced estrus response and conception rate as compared  to supplementation of minerals and bypass fat alone. Biherbal therapy (pulverized Curry leaves and Bael leaves, 1:1) @ 200 g/day for  5 days modulated genital health and improved estrus expression and conception rate in anestrus, repeat breeding and endometritic  bovines (n=75). With respect to molecular identification of fertility marker gene tried in more than 550 animals, targeting 6 specific  genes, only LHCGR3 showed appreciable difference in gene frequencies between fertile and infertile crossbred HF cattle. ‘T’ allele was  more prevalent in infertile crossbred cattle (50%), and ‘C’ allele in fertile crossbred cattle (100%). However, no such differences were  observed in indigenous cattle and buffalo. It was also validated on 83 crossbred calves below 1 year of age by revealing genotype  frequency of CC, TT and CT as 0.70, 0.11 and 0.19, and allele frequency for T and C allele as 0.20 and 0.80, respectively, predicting 80%  of tested calves fertile. Thus, SNP ‘T’ in LHCGR3 may be involved in infertility at least in crossbred cattle.
Keywords: Dairy animals; Fertility gene; Gujarat; Infertility amelioration; Nutritional supplement; Reproductive problems